DIAGNOSA KESULITAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA DAN UPAYA MENGATASINYA MENGGUNAKAN SCAFFOLDING - Abi, Alfonsa Maria (RANGE: Jurnal Pendidikan Matematika, 2020)
Student’s difficulties in finishing the problem of mathematics is a problem that cause student’s are not able to finish their difficulties of learning mathematics. The purpose of this study is to diagnose student’s difficulties in learning about teorema pythagoras of VIIIFSMP Negeri 1 Amanuban Barat. The subjects consist of 17 student’s. The method that use in this study is qualitative with approach of case study. The instruments that use in this study are observation, test, interview while for analise the data use Miles and Huberman model. The study revealed that student’s have less accuration in determining size of pictures and not able to make a conclusion. Based on students difficulties, to overcome those problems the researcher use the prosess of scaffolding to solve their problem in learning mathematics, such us: (1) asking student’s to find their difficulties in mathematic, (2) giving student’s oppourtunity to think logicaly, (3) giving some instruction questions in order to student’s are able to use the appropriate mathematics concept. (4) asking student’s to reflex their own answers to find their problem and difficulties. ( 5) asking student’s to repair their the result of test, and (6) asking student’s to examine again their result of test. Sixth treatments scaffolding able to assist the difficulty to lessen student’s especially to mathematics concepts that had to be studied. Scaffolding giving according to continue so that able student’s to finish it mathematics problem. Keywords : Diagnosa student’s difficulty, the problem of mathematics, and scaffolding.